The Effect of Cucumber Juice Administration on Hypertension Reduction in Menopausal Women in Kwala Begumit Village, Randu Gapit Hamlet, Stabat District, Langkat Regency 2024 - Hajar, Siti; Tarigan, Dwi Feni Pebriani Br (Institute of Accounting Research and Novation (IARN), 2025)
Background: Hypertension is a condition where a person's blood pressure is above the normal rate. It can be treated using herbal treatments such as cucumber juice. According to World Health Organization data reports at least 839 million cases of hypertension, estimated to be 1.15 billion in 2025 or about 29% of the total world population, where sufferers are more in women (30%) than men (29%). Data in Indonesia shows that 25.8% of populations over the age of 18 are hypertension sufferers and from the provincial classification it is known that 26.4% are in Java. Objectives: This research aims to determine the effect of drinking cucumber juice on reducing hypertension. Method; This research was quantitative study using a pre-experimental design with one group pre-post test approach. This study used analytical survey research with cross sectional approach. Data collected using observation sheets. The populations were all menopausal mother amount 13 people and all were sampled (total population). Data analysis used Wilcoxon test. Results: The results showed differences in the average value of hypertension reduction before and after cucumber juice was given, from 30.8 to 92.3. Wilcoxon test results obtained A-Asymp Sig (2-tailed) value was p=.005 (<.050). Conclusion: The conclusion shows that there is an effect of drinking cucumber juice on reducing hypertension. Suggestion for respondents to increase their knowledge in managing hypertension using non-pharmacology, for institutions to add information on the benefits of cucumber juice in reducing hypertension, and for further researchers to develop it further.